2001
DOI: 10.1177/0265407501181006
|View full text |Cite
|
Sign up to set email alerts
|

Are Attachment Styles General Interpersonal Orientations? Applicants' Perceptions and Emotions in Interaction with Evaluators in a College Entrance Examination

Abstract: This study examined whether attachment styles, constructed in close relationships, are related to applicants' perceptions and emotions in a substantially different relationship with evaluators in a college entrance examination. The findings suggest that secure and fearful styles may consist of somewhat stable interpersonal orientations that are evident across relationships. Fearful attachment was related to lower anticipatory challenge appraisal, more negative emotional reactions, and a less positive view of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Both sets of investigators, Tidwell, Reis, and Shaver (1996) and Pietromonaco and Barrett (1997), found that anxious and avoidant participants experienced fewer positive emotions than secure participants. Moreover, Rom and Mikulincer (2003) reported that both attachment anxiety and avoidance were associated with relatively low positive emotional tone during group interactions, and Horppu and Ikonen-Varila (2001) found that a combination of high anxiety and high avoidance (fearful avoidance) was associated with fewer positive emotions during a college entrance interview.…”
Section: Emotional Reactions To a Partner's Positive Behaviorsmentioning
confidence: 99%
“…Both sets of investigators, Tidwell, Reis, and Shaver (1996) and Pietromonaco and Barrett (1997), found that anxious and avoidant participants experienced fewer positive emotions than secure participants. Moreover, Rom and Mikulincer (2003) reported that both attachment anxiety and avoidance were associated with relatively low positive emotional tone during group interactions, and Horppu and Ikonen-Varila (2001) found that a combination of high anxiety and high avoidance (fearful avoidance) was associated with fewer positive emotions during a college entrance interview.…”
Section: Emotional Reactions To a Partner's Positive Behaviorsmentioning
confidence: 99%
“…Persons high in RS judged insensitive behavior of partners as more intentionally hurtful than those with low RS, and this led to more subsequent relationship conflicts (Downey & Feldman, 1996). Another study found that fearful attachment style was related to negative trait appraisal of evaluators during a college entrance examination (Horppu & Ikonen-Varila, 2001). It is possible that fearful attachment style and RS are partly overlapping constructs because both involve a longing for intimacy and a fearful expectation of rejection (Agrawal, Gunderson, Holmes, & Lyons-Ruth, 2004).…”
Section: Rejection Sensitivity Bpd and Trait Appraisalmentioning
confidence: 99%
“…The social cognitive processes in patients with BPD are characterized by negative appraisals of the emotions, motivations, or intentions of others (e.g., Arntz & Veen, 2001; Donegan et al, 2003; Wagner & Linehan, 1999). These types of social cognitive biases are associated with insecure adult attachment patterns (e.g., Horppu & Ikonen-Varila, 2001; Meyer et al, 2004; Mikulincer & Shaver, 2001; Niedenthal, Brauer, Robin, & Innes-Ker, 2002) and may directly relate to the occurrence of chronic negative affect and impulsivity. Accordingly, several studies have shown that insecure attachment patterns are related to high trait levels of negative affect or neuroticism (e.g., Adam, Gunnar, & Tanaka, 2004; Hagekull & Bohlin, 2003; Shaver & Brennan, 1992; Stams, Juffer, & van IJzendoorn, 2002) as well as aggressive behavior (Lyons-Ruth, 1996), anger (Mikulincer, 1998b), heightened emotional distress and anxiety when accessing negative memories (Mikulincer & Orbach, 1995), and heightened cortisol reactivity in response to psychosocial stress (e.g., Gunnar, Brodersen, Nachmias, Buss, & Rigatuso, 1996; Hertsgaard, Gunnar, Erickson, & Nachmias, 1995).…”
mentioning
confidence: 99%